An investigation into student perceptions towards mathematics and their performance in first year chemistry: introduction of online maths skills support. Issue 4 (22nd September 2016) - Johnston, Peter R.; Watters, Dianne J.; Brown, Christopher L.; Loughlin, Wendy A.
Abstract : An online Maths Skills Site was developed as an integrated support programme for first year Chemistry students, the content of which, was based on an analysis of their high-school mathematical backgrounds. This study examined the students' perceptions of Maths, their patterns of usage of the Maths Skills Site and whether there was a relationship between usage of the site and performance in first year chemistry. A questionnaire and surveys were administered to obtain data on student perceptions, confidence and anxiety. Hit-count tracking was enabled for the Maths Skills Site items (notes, questions, answers, online multiple choice questions), to establish usage patterns for the cohort and individuals, over time and against topic (significant figures, algebra, etc. ). Student perceptions changed over the semester. Increased confidence with chemistry and mathematics was observed, however, a significant proportion were still anxious when having to answers questions requiring calculations. Students who were already confident did not use the Maths Skills Site, whereas the students who did use the site displayed improved achievements in the credit grade category, as compared to non-users and employed a self-directed approach, tailoring their individual learning around topics important to them.